A collaborative approach towards prevention of otitis media in Aboriginal children. (1st October 2020) - Stroud, Victoria; Adams, Josie; Champion, Doreen; Hogarth, Geraldine; Mahony, Anne; Monck, Ruth; Pinnegar, Trulie; Weeks, Sharon; Watson, Charles
ABSTRACT: Otitis media is very common in Aboriginal children in Western Australia and chronic ear disease causes major problems in speech and language development and education. Up until recently, most programmes dealing with the problem of OM have focused on clinical interventions rather than prevention. The Enhanced Prevention Working Group was established as part of the WA Child Ear Health Strategy (2017–2021). The Group has worked collaboratively to develop a set of recommendations for prevention of OM in Aboriginal children. These recommendations were informed by WA-based health promotion interventions initiated by Aboriginal Health Practitioners at a community level. This paper provides a historical perspective of the current situation and discusses each of the recommendations from Aboriginal Health Practitioners working within their community.